The effect of spiritual intelligence and good organizational citizenship on employees' performance. - Amran, Atiela; Azhari, Nurul Nadhira Amalin; Abdullah Thani, Ayu Kamareenna; Rosely, Nur Hidayah; smail, An Nur Nabila; Nik Mohd Zainordin6, Nik Mohd Shamim; Nik Mohd Faris , Nik Mohd Faris; Ishak, Muhammad Ammar Haidar (Journal of Islamic, Social, Economics and Development, 2025)
Employees play a crucial role in an organization's success, and management should prioritize their importance. Research suggests that spiritual intelligence and organizational citizenship behavior (OCB) enhance employees’ performance. A study was conducted at Ministry of Finance (MOF), Putrajaya. A total of 343 public servants from Ministry of Finance, Putrajaya were surveyed to gather data. The research model hypotheses were tested using SPSS 27 for data analytics. The study emphasizes a notable and positive relationship between spiritual intelligence and both organizational citizenship behavior (OCB) and employees’ performance. OCB has been demonstrated to serve as a complementary mediating factor in the relationship between spiritual intelligence and employees’ performance. This finding suggests that the spiritual intelligence of an organization significantly predicts its citizenship behavior. The results of this study enhance the existing body of knowledge and provide new opportunities for further investigation.